Market readiness and opportunities for air purifiers marketed by Singer Bangladesh Limited - Rummat, Shadman Sakib (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.